TIMBRE VARIATION OF PRETONIC MIDDLE VOWELS IN AN AMAZONIAN CONTEXT: ANALYTICAL APPROACHES TO THE LINGUISTIC PRAXIS OF MALE AND FEMALE WORKERS - Rodrigues, Doriedson do Socorro (Revista de Letras, 2024)
We present the results of an investigation on the pretonic middle vowels /e/ and /o/, analyzing the variation of timbre, open and closed, in correlation with gender inflection, from the Portuguese spoken in the municipality of Cametá, Pará. We inquire about how linguistic and social factors act in the configuration of the variation under examination, based on the theoretical assumptions of Labovian sociolinguistics. Speech data were obtained from 36 interviewees, socially stratified in terms of education, age, origin and gender. The results point to a higher probability of closed timbre and with greater performance with female speakers, aged 46 years and above, with schooling with elementary education, both in urban and rural areas. Linguistically, closed timbre is more likely to occur in words whose gender is marked by the presence of the morpheme –a or its absence, to the detriment of gender marked by other linguistic strategies. Keywords: Language. Amazon. pretonic media. Variation. Timbre. Gender Suppression.